FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN PROPERTI DAN REAL ESTATE - Sprang, Marcell Julio Fredericus Van; Widyasari, Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study is to empirically prove the effect of profitability, asset structure, free cash flow and leverage on financial distress in properties and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sample used in this research is as many as 60 sample data selected by purposive sampling method which valid data was 20 companies. Data processing techniques in this study using multiple regression analysis and t test that helped by Eviews 12 program and Microsoft Excel 2010. The results of this study show that profitability and free cash flow have significant positive effect on financial distress, asset structure has insignificant negative effect on financial distress, and leverage has insignificant positive effect on financial distress. The implication of this study is the higher the profitability and free cash flow, will increase the chance of companies to avoid financial distress which will give investor a good signal.